Theoretical and methodological approaches to the study of the phenomenon of ethnic identity (Journal of Philosophy Culture and Political Science, 2016)
In given article various theoretical and methodological approaches of research of a phenomenon of identity in philosophy are considered.The analysis of various approaches to national identity, its many-sided nature are given. In research the analysis of process where identity is considered as a philosophical category, as a category of social nowledge, as a psychological category in various philosophical discourses of foreign and domesticresearchers is carried out. Process of formation of individual identity and its components is analyzed.Identity from a position of approaches primordialism and constructivism is considered. Attempt to deepen onceptual sense of socially-philosophical researches of national identity and to open the essence of a phenomenon of ethnic identityis undertaken. Considering an identity phenomenon in all its complexity and variety, allocating its communication with the external, social world and private world, subjectivity of the person, the particular interest is caused by classical works devoted to the given problematics.
Keywords: identity; sameness; consciousness; ethnic identity; a society; subjectivity; the concept